Pharmacokinetic, toxicological and pharmacodynamic analysis of flavonoid quercetin isolated seeds of Bixa orellana l. (Research, Society and Development, 2020)
The present study aimed to analyze in silico the pharmacokinetic and toxicological properties of quercetin flavonoid isolated from Bixa orellana seeds in order to observe the feasibility of this metabolite as a candidate for non-treatment of dyslipidemia. In addition, to endorse pharmacodynamics by means of molecular docking at HMG-CoA be reduced or by comparing as a reference drug sinvastatin and proposed or according to its mechanism of ação. For a pharmacokinetic and toxicological analysis, use the PreADMET online server and perform the predições as a basis for the structure and activity of molecules. A pharmacodynamic analysis was carried out by means of computational docking using AutoDock Vina software to obtain molecular structures and energy from target-ligand complexation. According to two ADME results, a quercetin shows pharmacokinetic and toxicological results next to sinvastatin. Either molecular docking indicou or energy value of binding of the most stable pose to the flavonoid and the target being –8.8 kcal / mol while that with sinvastatin presented the energy of –6.6 kcal / mol, evidencing that quercetin binds more stabilization of the active agent or commercial drug. A variation of the relationship between the two statistically significant binders with P